2018
DOI: 10.1055/a-0608-5292
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Antiseptics in the Prophylaxis of Infection in Orthopaedic Surgery

Abstract: Although no clear regimen can be recommended, the available literature indicates that the use of intraoperative topical antiseptics is of clinical relevance in preventing infection of orthopaedic implants. Further randomised controlled trials are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…As this chemical has no associated adverse effects, they concluded that this method is a safe and inexpensive method to reduce the infection rate. However, a clear regimen or procedure cannot be recommended based on the current literature 16. Secondly, an instrument or an implant falling to the ground will increase surgical duration.…”
Section: Discussionmentioning
confidence: 99%
“…As this chemical has no associated adverse effects, they concluded that this method is a safe and inexpensive method to reduce the infection rate. However, a clear regimen or procedure cannot be recommended based on the current literature 16. Secondly, an instrument or an implant falling to the ground will increase surgical duration.…”
Section: Discussionmentioning
confidence: 99%
“…A significant reduction in wound infection rates can be achieved with different antiseptic irrigations prior to wound closure (12). Three other reviews conclude that the available literature shows that the use of intraoperative topical antiseptics is of clinical relevance to prevent infection of orthopedic implants (30)(31)(32). A meta-analysis of 20 studies of instrumented spine surgery showed that topical antibiotics can reduce the risk by threefold, while antiseptic irrigation with povidone-iodine can reduce the risk of wound infection by sevenfold (33).…”
Section: Antisepticsmentioning
confidence: 99%